Evaluation of the knowledge of sun exposure and sun protective measures in healthcare workers - Eliz Aryal; Prashanna Raj Shrestha; Sujan Gautam (Occupational Health and Safety Society of Nepal, 2023)
Introduction: Solar ultraviolet (UV) radiation has a great impact on human life. The sun has always played an important role in Asian culture, so much so, that it is often prayed to as a God. Prolonged sun exposure can cause extensive and chronic harmful effects. Healthcare personnel is supposed to have good knowledge regarding sun protection as they play a key role in society disseminating knowledge to the general public. There are limited data regarding the knowledge of sun protection and sunscreen practice among health care workers. Methods: This descriptive cross-sectional study was carried out from June to October 2020 on healthcare workers (medical staff) in Kathmandu Medical College Teaching Hospital. A questionnaire was distributed to the target study population without disturbing or hampering the healthcare worker's duty. Results: Out of a total of 264 participants in the study, 84 (31.8%) were male and 180 (68.2%) were female. The knowledge of proper terminology for SPF (Sun Protection Factor) was noted in 196 (74.2%) and 57 (21.6%) agreed that the value of SPF was related to age. No significant difference was noted regarding knowledge about the time of sun exposure for Vitamin D synthesis. No significant differences were found in practices of sunscreen use for purposes of fairness, or prevention of tanning, wrinkle, mole, and skin cancer. Conclusion: A higher level of education was associated with better knowledge and proper abiding practices regarding sunscreen use. As healthcare workers play a key role in distributing information in society, they should be targeted in education campaigns regarding sun exposure and sun protection measures; with these efforts focused more on nurses and medical officers.